Diversity, Chemical Constituents, and Biological Activities of Endophytic Fungi Isolated From Ligusticum chuanxiong Hort - Tang, Zizhong; Qin, Yihan; Chen, Wenhui; Zhao, Zhiqiao; Lin, Wenjie; Xiao, Yirong; Chen, Hong; Liu, Yuntao; Chen, Hui; Bu, Tongliang; Li, Qingfeng; Cai, Yi; et al. (Frontiers in Microbiology, 2021)
The objective of this study was to evaluate the diversity of endophytic fungi of different parts of Ligusticum chuanxiong Hort (CX) and identify chemical compounds produced by endophytic fungi and their biological activities. As a result, a total of 21 endophytic fungi were isolated and identified from CX. Penicillium oxalicum, Simplicillium sp., and Colletotrichum fructicola were screened for promising strains by the color reaction. Comparison between the different organic extracts of the three strains, it was observed that the ethyl acetate extracts of Penicillium oxalicum and Simplicillium sp. and the n-butanol extracts of Colletotrichum fructicola showed significant antioxidant and antibacterial activity. The ethyl acetate extracts of Penicillium oxalicum had outstanding antioxidant and antibacterial effects, and its radical scavenging rates for ABTS and DPPH were 98.43 ± 0.006% and 90.11 ± 0.032%, respectively. At the same time, its IC50 values were only 0.18±0.02 mg/mL and 0.04±0.003 mg/mL. The MIC of the ethyl acetate extract of Penicillium oxalicum against Escherichia coli and Staphylococcus aureus is only 0.5 mg/mL. Through LC-MS, we found that Penicillium oxalicum could produce many high-value polyphenols, such as hesperidin (36.06 μmol/g), ferulic acid (1.17 μmol/g) and alternariol (12.64 μmol/g), which can be a potential resource for pharmaceutical industries. In a word, the results increase the diversity of CX endophytic fungi and the antioxidant and antibacterial activitity of their secondary metabolites, which provide new ideas for the discovery of new natural active substances from endophytic fungi, such as antioxidants and antibacterial substances, or the production of better and more drugs from CX.